Psychological Help for a Person in a State of Acute Crisis - Zaushnikova Marina Yurievna; Petukhova Irina Alekseevna (European Journal of Life Safety and Stability (2660-9630), 2022)
The relevance of this article is due to the fact that in the modern world, psychological assistance in crisis situations is becoming more and more necessary. Overcoming a crisis, a person can gain new experience, improve stress resistance and expand the arsenal of behavioral responses. Most often, a person can independently overcome a crisis state, but in some cases, a crisis event can lead to psychological trauma (psychotrauma). Psychic trauma is an experience of a special kind, the result of a special interaction between a person and the world around him. This is a normal reaction to abnormal, difficult, traumatic circumstances, a condition that occurs in a person who has experienced something that is beyond his normal life experience. This stress, according to the intensity of the feelings experienced, seems to be the most significant event in life, dividing a person’s whole life into “before and after”. The resulting psychic trauma changes the vision of not only the present, the past, but also the future. This is such a severe blow that the person loses the ability to continue a normal life. The symptoms of a traumatic event experienced are manifested in each person individually, but there is a classification of common signs. The provision of psychological assistance to people who have experienced a traumatic event and are in an acute crisis state is primarily aimed at reducing the risks of post-traumatic disorders in the future, as well as developing stress tolerance so that a person can adapt to stressful events and overcome them. To this end, psychologists recommend using the universal BASIC PH model, based on a multimodal approach and including six resource channels, where a person needs to recognize his dominant resource channels and rely on them for a speedy recovery.